Vegetable soybean tolerance to flumioxazin-based treatments for waterhemp control is similar to grain-type soybean. (June 2019) - Williams, Martin M.; Moody, James L.; Hausman, Nicholas E.
Abstract: Herbicides registered in vegetable soybean often fail to control waterhemp. The objective of this research was to quantify vegetable soybean tolerance to preemergence herbicides for early-season waterhemp control, including flumioxazin applied alone PRE or in mixture with chlorimuron, metribuzin, or pyroxasulfone at use rates in grain-type soybean. Crop tolerance to the herbicides was tested in field trials with 20 vegetable soybean cultivars and four grain-type cultivars through 4 wk after treatment (WAT). Flumioxazin-based treatments were equally safe, resulting in only minor, transitory crop response (<5% injury 2 WAT) and no effect on crop emergence or early season growth. Flumioxazin mixtures provided greater than 99% control of waterhemp 4 WAT, as evidenced by reduced weed density from 29.7 plants m −2 in the nontreated control to no waterhemp. Flumioxazin applied alone or in tank mixture with chlorimuron, metribuzin, or pyroxasulfone were as safe in vegetable soybean as previously reported in grain-type soybean. Registration of these products in vegetable soybean would provide the industry with additional options for managing waterhemp.